THE ROLE OF SOCIAL SKILLS IN ENHANCING MANAGERIAL PERFORMANCE THROUGH TRANSFORMATIONAL LEADERSHIP CHARACTERISTICS: A DEVELOPING COUNTRY PERSPECTIVE (The South East European Journal of Economics and Business, 2025)
Although a significant number of studies analyzing the impact of transformational leadership on job performance has been recognized, there is a lack of research considering this construct in the context of managerial performance, and along with interpersonal characteristics. To fill this gap, this paper has been built on Mintzberg’s (1973) premise according to which interpersonal skills play an important role in achieving not only managerial performance but also their leadership styles. In other words, it has been argued that transformational leadership behaves as a mediator in the relationship between social skills and managerial performance. Given the main findings, the paper contributes to practical thinking by indicating the importance of including social skills training focused on building social flexibility and presentation skills, so that managers could have a greater positive impact on managerial performance. As a consequence, it is well known that their better performance increases overall organizational success, which is a valuable lesson for a developing country setting in which this research has been conducted. Contributions to theory and practice are offered after which direction for further research follows.